EFFICIENCY OF LOW-COST ADSORBENT MATERIALS FOR HYDROGEN SULFIDE REMOVAL FROM BIOGAS USING A FIXED BED ADSORPTION COLUMN - Phothilangka, Phimphaka (Life Sciences and Environment Journal, 2025)
This research aimed to test the efficiency of locally available, low-cost and efficient adsorbents suitable for removing hydrogen sulfide from biogas produced as an alternative energy source in livestock farms. The adsorbent materials tested were concrete pellets, steel wool, wood chips and diatomite. The efficiency of the adsorbent was compared with the adsorbent that has been improved by coating with ferric hydroxide to study the removal of hydrogen sulfide in biogas. The tests were performed by loading the adsorbent in a fixed bed adsorption column with a diameter of 10.16 cm and a length of 50 cm, allowing biogas to flow through by 15-20 liters per minute (900-1,200 liters/hour). The results showed that the ferric hydroxide-coated concrete pellets packed in the column can effectively remove hydrogen sulfide in biogas, with an average removal of 99.18% of hydrogen sulfide before entering the system at an average concentration of 2,551 ppm.